Separations of non-monotonic randomness notions - Bienvenu, Laurent; Hölzl, Rupert; Kräling, Thorsten; Merkle, Wolfgang (Journal of logic and computation, 2012)
Abstract. In the theory of algorithmic randomness, several notions of random sequence are defined via a game-theoretic approach, and the notions that received